Stress distribution analysis on the one-stage non-submerged and two-stage submerged system implant supported bridge - Prihatono, Joko; Sumarsongko, Taufik; Dirgantara, Tata Cipta; Rikmasari, Rasmi (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2018)
Introduction: Tooth restoration and implant-supported was one of the methods to overcome the free end cases. Abutment and implant are two components that are fused together by a screw. Therefore, the main problem to solve are loosened screw and implant or abutment fracture because of increasing unpredictable potential force on the implant, abutment, and screw. The purpose of this research was to describe the distribution stress between the connection of the body of implant and abutment on the submerged and non-submerged design of the implant supported bridge. Method: The submerged and non-submerged design implant have been analyzed using the Finite Element Method under lateral and vertical static load for 180 N. The numeric model for lower jaw posterior segmented bone was determined by computed tomography, and the load measurement was performed to observe the distribution at the connection between the body of implant and the abutment of the implant supported bridge submerge and non-submerged design. Results: At the lateral load, the distribution strength value was 1.562x107 Pa, whilst for the non-submerged was 9.63x107Pa. At the vertical load, the distribution strength value was 1.038x107 Pa, whilst for the non-submerged was 3.342x107Pa. At the load of 180 N towards the vertical and lateral on the supported implant bridge, the distribution strength value had a smaller scale compared to the ultimate tensile strength (UTS), which was 1040 MPa (1.04 x 109 Pa). Conclusion: Both of the design including the secondary component (abutment) was safe to used as the supporting implant bridge.